Perbedaan Kejadian Perdarahan Dan Infeksi Tali Pusat Yang Diikat Dengan Benang Dan Umbilical Cord Clamp - Ni Made Lisfasiska; Siti Asiyah (coba, 2013)
The use of two different methods of tying the umbilical cord has different consequences for the emergence of the risk of bleeding and infection in the umbilical cord. This research objective is determining the differences of bleeding and umbilical cord infection that has bound with yarn and umbilical cord clamp . Population studied were all babies born in hospitals Pare and RS Gambiran on the date of July 1 to 29, 2013, by using accidental sampling technique obtained sample was 23 respondents consisting of 11 respondents from hospitals Pare and 12 respondents from hospitals Gambiran. The data was collected using observation sheets, the results are then analyzed using fisher exact. The results of analysis shown that (p = 0,522) > (α = 5%), so that there was no significant difference in the binding of a baby with umbilical cord bleeding events in hospitals and hospitals Gambiran Pare. The results of analysis shown that (p = 0,522) > (α = 5%) , so there was no significant differences in binding of the baby's umbilical cord with the incidence of infection in hospitals and hospitals Gambiran Pare. Expected for healthcare institutions that still use nylon thread to tie the umbilical cord, can replace the use of umbilical cord clamp because of a risk of bleeding and infection was lower when care at home. Keywords : Umbilical Cord Binding, Bleeding, Infection